2020
DOI: 10.1155/2020/4169691
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Tumorigenesis and Prognosis-Related Genes of Lung Adenocarcinoma: Based on Weighted Gene Coexpression Network Analysis

Abstract: Lung adenocarcinoma is the most frequently diagnosed subtype of nonsmall cell lung cancer. The molecular mechanisms of the initiation and progression of lung adenocarcinoma remain to be further determined. This study aimed to screen genes related to the progression of lung adenocarcinoma. By weighted gene coexpression network analysis (WGCNA), we constructed a free-scale gene coexpression network to evaluate the correlations between multiple gene sets and patients’ clinical traits, then further identify predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 48 publications
1
37
0
Order By: Relevance
“…Telomere C-strand (Lagging Strand) Synthesis and E2F-mediated regulation of DNA replication are some of its related pathways. A previously conduced weighted gene co-expression network analysis revealed that it was a prognosis-related biomarker in lung adenocarcinoma (Yi et al, 2020). However, our GEPIA survival analysis showed that RFC4 overexpression was positively correlated with pathological staging but was not associated with poor prognosis in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 55%
“…Telomere C-strand (Lagging Strand) Synthesis and E2F-mediated regulation of DNA replication are some of its related pathways. A previously conduced weighted gene co-expression network analysis revealed that it was a prognosis-related biomarker in lung adenocarcinoma (Yi et al, 2020). However, our GEPIA survival analysis showed that RFC4 overexpression was positively correlated with pathological staging but was not associated with poor prognosis in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 55%
“…Telomere C-strand (Lagging Strand) Synthesis and E2F-mediated regulation of DNA replication are some of its related pathways. A previously conduced weighted gene coexpression network analysis revealed that it was a prognosis-related biomarker in lung adenocarcinoma (Yi et al, 2020). However, our GEPIA survival analysis showed that RFC4 overexpression was positively correlated with pathological staging but was not associated with poor prognosis in patients with lung adenocarcinoma.…”
Section: Analysis Of the Mechanism Of Hub Genes In The Tcga Databasementioning
confidence: 54%
“…Regarding lung cancer, several researches con rmed that CDCA5, exhibiting high speci city and sensitivity to distinguish malignant lesions from non-malignant tissues and associated with poor survival, could be identi ed as predictive biomarkers for tumorigenesis and poor prognosis of lung adenocarcinomas [13,14]. In study performed by Nguyen et al, suppression of CDCA5 expression inhibited the growth of lung cancer cells; concordantly, induction of exogenous expression of CDCA5 conferred growth-promoting activity in mammalian cells.…”
Section: Discussionmentioning
confidence: 99%